On ultraconnected spaces - P. M. Mathew (International Journal of Mathematics and Mathematical Sciences)
In this paper, we study some properties of ultraconnected spaces and show that ultraconnected T12 spaces are maximal ultraconnected and minimal T12. We also introduce the notion of F-connected spaces, topological spaces wich are both hyperconnected and ultraconnected and characterize compact maximal F-connected topologies on a set.